The Use of Seismic Reflection Data Inversion Technique to Evaluate the Petro- Physical Properties of Nahr Umr Formation at Kumait and Dujaila Oil Fields – Southern Iraq - Nassir, Nowfal A.; AL- Banna, Ahmed S.; Al-Sharaa, Ghazi H. (Iraqi Journal of Science, 2021)
The estimation of rock petrophysical parameters is an essential matter to characterize any reservoir. This research deals with the evaluation of effective porosity (Pe), shale volume (Vsh) and water saturation (Sw) of reservoirs at Kumait and Dujalia fields, which were analyzed from well log and seismic data. The absolute acoustic impedance (AI) and relative acoustic impedance (RAI) were derived from a model which is based on the inversion of seismic 3-D post-stack data. NahrUmr formation’s sand reservoirs are identified by the RAI section of the study area. Nahr Umr sand-2 unit in Kumait field is the main reservoir; its delineation depends on the available well logs and AI sections information. The results of well logging interpretation showed a decrease of Sw and Vsh and an increase of effective porosity in the oil reservoir area, which coincides with the decrease of AI values. The existence of the water reservoir in Du-2 well revealed a convergence of the results of AI and effective porosity with those of Kumait wells , along with and some differential results of Sw and Vsh values that may be related to changes in lithology and fluid density.